Diplomasi Kerjasama Indonesia-Korea Selatan Dalam Pengadaan Alutsista (2019-2022) - Satria, Yogi; Yunanto, Sri (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
Procurement of primary equipment in the defense industry is one thing that is no less important that must be considered by every country to maintain its sovereignty and security. So far, Indonesia's defense system is still less than optimal, so it requires cooperation. The purpose of this study is to examine how Indonesia-South Korea's diplomatic cooperation in the Procurement of Defense Equipment 2019-2023. By using the theory of National Interest, Military Capability, and Defense Cooperation, the results of this study are to improve Indonesia's defense capabilities in collaboration on defense cooperation in the procurement of defense equipment. Indonesia is trying to increase the MEF in the RPJM in the era of President Jokowi. The government has shown its commitment to building and developing an independent defense industry. The Indonesia-South Korea cooperation is a promising cooperation, PT. Pindad and Daewoo Shipbuilding can share knowledge, technology (ToT), and experience Keywords: Cooperation, Defense Equipment, Transfer Of Technology, South Korea